A novel Link of Serum IL-39 Levels in Patients with Rheumatoid Arthritis - Al Ghuraibawi, Zahraa Adnan Ghadhban; Sharquie, Inas K.; Gorial, Faiq I. (Iraqi Journal of Science, 2023)
Rheumatoid arthritis (RA) is an inflammatory condition causing joint pain and stiffness, with often debilitating and life-limiting consequences. Recently, a new B-cell secreted cytokine, IL-39, was identified in mice. The most up-to-date research indicates that although IL-39 is expressed in murine models of lupus and has a role in mediating the inflammatory response in this context, there is no solid, replicated evidence of the existence of IL-39 in humans. This study aimed to clarify the existence and role of IL-39 in the human body and to elucidate whether it plays a role in rheumatoid arthritis. Accordingly, serum samples were collected from 66 patients with rheumatoid arthritis who were under therapy and from 66 healthy controls attending the Baghdad Teaching Hospital Rheumatology Unit. Enzyme-linked immunosorbent assay (ELISA) was used to detect serum levels of IL-39. Our results showed that mean ages of RA patients were 46.48 ± 10.17 years, and for healthy controls 44.97 ± 11.658 years. The results revealed that serum IL-39 levels were significantly lower in RA patients (p = 0.016) (4.95 ± 1.1001) compared to healthy controls (5.55 ± 1.762). Corresponding sensitivity of IL-39 was 56.1%and specificity was 60.6% at cutoff values of ≤ 4.99 ng/ml. In Conclusion, IL-39 is found in humans but is downregulated in rheumatoid arthritis patients. This suggests either that IL-39 can have both pro- or anti-inflammatory functions based on the underlying disease or that the role of IL-39 is masked by the effects of treatment.